Interaction between the Water Soluble Poly{1,4-phenylene-[9,9-bis(4-phenoxy butylsulfonate)]fluorene-2,7-diyl} Copolymer and Ionic Surfactants Followed by Spectroscopic and Conductivity Measurements - Tapia, M. J. (2005)
The interaction has been studied in aqueous solutions between a negatively charged conjugated polyelectrolyte poly{1,4-phenylene-[9,9-bis(4-phenoxybutylsulfonate)]fluorene-2,7-diyl} copolymer (PBS-PFP) and several cationic tetraalkylammonium surfactants with different structures (alkyl chain length, counterion, or double alkyl chain), with tetramethylammonium cations and with the anionic surfactant sodium dodecyl sulfate (SDS) by electronic absorption and emission spectroscopy and by conductivity measurements. The results are compared with those previously obtained on the interaction of the same polymer with the nonionic surfactant C12E5. The nature of the electrostatic or hydrophobic polymer−surfactant interactions leads to very different behavior. The polymer induces the aggregation with the cationic surfactants at concentrations well below the critical micelle concentration, while this is inhibited with the anionic SDS, as demonstrated from conductivity measurements. The interaction with cationic surfactants only shows a small dependence on alkyl chain length or counterion and is suggested to be dominated by electrostatic interactions. In contrast to previous studies with the nonionic C12E5, both the cationic and the anionic surfactants quench the PBS-PFP emission intensity, leading also to a decrease in the polymer emission lifetime. However, the interaction with these cationic surfactants leads to the appearance of a new emission band (525 nm), which may be due to energy hopping to defect sites due to the increase of PBS-PFP interchain interaction favored by charge neutralization of the anionic polymer by cationic surfactant and by hydrophobic interactions involving the surfactant alkyl chains, since the same green band is not observed by adding either tetramethylammonium hydroxide or chloride. This effect suggests that the cationic surfactants are changing the nature of PBS-PFP aggregates. The nature of the polymer and surfactant interactions can, thus, be used to control the spectroscopic and conductivity properties of the polymer, which may have implications in its applications.